Terreiros: memórias e representações no espaço sagrado - Honaiser, Fernando Alves (2006)
The space of Terreiro is an unique space, in the social context, due to its controversy of the diversity and possibility of comprehension. The present study analyzes the space of the Umbanda´s Terreiros of the city of Maceió through its imagetic representation built by two different social groups: the people who inhabit these spaces and those that don’t participate in its rites. For such analysis, a methodological apparatus was searched in order to make possible the understanding of the different facets of the image of the spaces of the Terreiro. This support was found in the field of the Social Representations, proposes by the social psychologist Serge Moscovici. In this context the importance of the historical-cultural study of the society was observed, to understand the processes that build the Social Representations. This study seeks to point the interdisciplinarity of the Inhabited Space, bringing to the debate different forms of representations of the space, through the analysis of the spaces of Terreiro, making possible the understanding of the projected image for different social spheres, including the space of Terreiro as landscape and body.